Get to the point : sharpen your message and make your words matter - Schwartzberg, Joel (BK business book., 2017)
Whether you want to improve your impact in speeches, staff meetings, pitches, emails, PowerPoint presentations, or any other communication setting, this book provides a novel approach that teaches you how to go from simply sharing a thought to making a difference. --